Strategy for Forming a Learning Organizational Culture at Bank Syariah Indonesia Branch Offices Jakarta Bendungan Hilir - Supriyatin Sy (SEAN Institute, 2023)
The purpose of this study is to identify the approach taken by PT Bank Syariah Indonesia Jakarta Bendungan Hilir Branch Office in order to cultivate a culture of learning throughout the company. The method of surveying, in which data are obtained from the outcomes of data collection using a questionnaire, was selected as the methodology for this research project. According to the findings of this study, learning organizations are affected by knowledge management. On the other hand, entrepreneurial orientation, transformational leadership, and management control systems do not have an effect on learning organizations. Knowledge management is the only factor that was found to have an effect on learning organizations. Consequently, the findings of the research simultaneously demonstrate that control management systems, entrepreneurial orientation, knowledge management, and transformational leadership each have a significant influence on the development of a learning organizational culture, which accounts for 71.9% of the total.